2015
DOI: 10.1007/s10803-015-2476-8
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder Symptoms Among Children Enrolled in the Study to Explore Early Development (SEED)

Abstract: This study examined the phenotypic profiles of children aged 30–68 months in the Study to Explore Early Development (SEED). Children classified as autism spectrum disorder (ASD), developmental delay (DD) with ASD symptoms, DD without ASD symptoms, and population comparison (POP) differed significantly from each other on cognitive, adaptive, behavioral, and social functioning and the presence of parent-reported conditions. Children with ASD and DD with ASD symptoms had mild to severe ASD risk on several measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 36 publications
7
45
1
Order By: Relevance
“…We found that more than 95% of children with ASD, independent of their age group, had at least one co-occurring condition/symptom identified in their records. However, the proportion found in our study was higher compared to some of these studies (Levy et al 2010; Simonoff et al 2008; Wiggins et al 2015). This may be due to a number of reasons, including, the type and number of co-occurring conditions/symptoms assessed and whether some of these co-occurring conditions/symptoms were combined in larger categories.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…We found that more than 95% of children with ASD, independent of their age group, had at least one co-occurring condition/symptom identified in their records. However, the proportion found in our study was higher compared to some of these studies (Levy et al 2010; Simonoff et al 2008; Wiggins et al 2015). This may be due to a number of reasons, including, the type and number of co-occurring conditions/symptoms assessed and whether some of these co-occurring conditions/symptoms were combined in larger categories.…”
Section: Discussioncontrasting
confidence: 95%
“…In line with other studies (Gurney et al 2006; Levy et al 2010; Lundstrom et al 2015; Nicholas et al 2009; Simonoff et al 2008; Supekar et al 2017; Wiggins et al 2015), we documented a high prevalence of co-occurring conditions/symptoms in those with ASD. As indicated by others (e.g., Levy et al 2010; Lundstrom et al 2015) and confirmed in our study, only a small proportion of children with ASD did not have any co-occurring condition/symptom.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The Study to Explore Early Development (SEED) is a multi-site case-control study designed to explore risk factors for the development of ASD (Schendel et al 2012; Wiggins et al 2015a, b). SEED presents a distinct opportunity to investigate ASD phenotypes because of its large sample size, comprehensive data collection, and thorough developmental assessment of child participants.…”
Section: Introductionmentioning
confidence: 99%